Modeling of ionizing radiation effect on static and dynamic behavior of vertical cavity surface-emitting lasers - Eladl, Sh.M.; Sharshar, K.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
In this work, the effect of ionizing radiation on the static and dynamic behavior of Vertical Cavity Surface Emitting Laser (VCSEL) was investigated numerically. First, the model of dynamic behavior before irradiation has been analyzed based on the Convolution Theorem. Second, all interesting ionizing radiation sensitive factors are compared with their corresponding post irradiation factors. The convolution theorem is applied to get features of dynamic behavior. All interesting parameters have been outlined. The effect of resonance frequency and damping parameters has been studied. The results show that the static and dynamic responses of these devices are dramatically deteriorated due to irradiation flux. The device gradually changes its mode of operation from lasing mode to LED mode by exhibiting weak oscillation of the output and fast damping with the increase of ionizing radiation. This type of model can be used for high data bit rate in a multimode optical fiber network.